An analysis of IT consultancy & entry strategy in Norwegian market : the case of start-up company - Shah, Shristi; Donyaprueth Krairit; e; Sununta Siengthai; Austrian Development Agency (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Globalization of business, focus on core competencies. TEO as software development company shall provide software development competencies to their ideal customer. Ideal customers are small-medium enterprises (SME) and particular Independent Software Vendor (lSV). TEO uniqueness is their software development approach is that they turn globalization in empowering software development strategy for smaller business which can benefits in development capacity.TEO mission is to have their sales office in multiple locations to provide different value proposition to their customer. TEO is looking forward for Norwegian market. After analyzing a lot it can be seen that TEO should enter Norwegian market, looking through market size there Norway is growing every year in terms of SME's and ICT sector and the demand is also very high for IT consultant and the maximum turnover of Norwegian economy is by SMEs. Even seeing the legal and political scenario it is stable. Even seeing the competitors' part though there are lots of competitors, there is still demand ofIT consultant and IT professionals, and Norway is still lagging behind in terms of ICT sector. Entering only is not the solution to do marketing is also very essential, creating value and pricing. TEO should have good organization structure. Though there is certain risk for TEO to enter Norwegian market but another name of business is risk and TEO can overcome the risk and have successful office setup in Norway
A project study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Project (M.B.A.) - Asian Institute of Technology, 2009
Keywords: Information technology -- Marketing -- Norway